2020
DOI: 10.1101/2020.04.09.20060137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An effect assessment of Airborne particulate matter pollution on COVID-19: A multi-city Study in China

Abstract: ≤ 2.5 μ m (PM 2.5 ) and ≤ 10 μ m (PM 10 ), ambient temperature (AT), absolute humidity (AH) and migration scale index (MSI) in 72 cities of China (excluded Wuhan city) on a daily basis, each of whichconfirmed more than 50 cases from January 20th to March 2nd, 2020. We applied a two-stage analysis. Generalized additive models with quasi-Poisson distribution was first fitted to estimate city-specific effects of PM 10 and PM 2.5 on daily confirmed COVID-19 cases while controlling AT, AH and MSI. Then, we used met… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 29 publications
1
27
1
3
Order By: Relevance
“…In China, in Hubei province, brand new time analyses give preliminary evidence of a correlation between high levels of NO2 and 12day delayed virus outbreaks 49 and other PM covariates 50,51 . In the U.S.A., levels of PM2.5 have just been found responsible for 20-time higher mortality rate by COVID-19, a rate much higher than other demographic co-variables 52 .…”
Section: Discussionmentioning
confidence: 99%
“…In China, in Hubei province, brand new time analyses give preliminary evidence of a correlation between high levels of NO2 and 12day delayed virus outbreaks 49 and other PM covariates 50,51 . In the U.S.A., levels of PM2.5 have just been found responsible for 20-time higher mortality rate by COVID-19, a rate much higher than other demographic co-variables 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Aerosols in recent times were confirmed as one of the Covid19 transmission routes that could be modified by the level of pollution of PM in air (23). The results of the research conducted in 72 cities in China found positive correlations between the PM 2.5 and PM 10 cases with the Covid19 case by taking into account the population migration factor and the meteorological factor (24). These results give the conclusion that it is possible that the PM pollution in the air affects the transmission of Covid19.…”
Section: Discussionmentioning
confidence: 94%
“…Correspondingly, higher mortality was also correlated with poor air quality, namely with high PM 2.5 , CO and NO 2 values [19]. In the same way, airborne particulate matter pollution likely increases the risk of getting COVID-19 in China [20]. COVID-19 held higher case fatality rate with increasing concentrations of PM 2.5 and PM 10 in temporal scale, which may affect the process of patients developed from mild to severe and nally in uence the prognosis of COVID-19 patients [21].…”
Section: Introductionmentioning
confidence: 92%